Terminology Adaptation in Green Halal Economy: Arabic – English to Indonesian: Adaptasi Terminologi dalam Ekonomi Hijau Halal: Bahasa Arab–Inggris ke Bahasa Indonesia - Cutri A. Tjalau; Hasna Nurain Mukhsin; Sri Hantuti Paramata (Language Development Center, 2026)
Background: The development of the Green Halal Economy in Indonesia has encouraged the intensified use of Arabic and English terms in regulations, academic discourse, and sustainable halal industry practices. However, this use of terms exhibits variations in transliteration and adaptation, potentially leading to conceptual ambiguity and policy inconsistencies. Purpose: This study aims to analyze the transliteration patterns and adaptation of Arabic–English terminology in Green Halal Economy practices in Indonesia and explain their linguistic and policy implications. Method: The research used a descriptive qualitative approach with an applied linguistics framework. Data were collected through a study of policy documents, halal certification standards, academic publications, industry texts, and semi-structured interviews. Data were then analyzed through term identification, source language classification, transliteration analysis, and semantic-pragmatic adaptation analysis. Results and Discussion: The results show that Arabic terms serve as normative and ethical foundations but tend to be conceptually adapted without consistent transliteration, while English terms serve as technical and systemic frameworks, the stability of which is heavily influenced by institutional authority. The discussion confirms that terminology constitutes non-material infrastructure in the governance of the Green Halal Economy. Conclusions and Implications: This study concludes that standardization of terminology is necessary to improve regulatory clarity, effectiveness of cross-sector communication, and sustainability of the halal industry in Indonesia.